Predictive Value of Adenoviral Load for Bronchial Mucus Plugs Formation in Children with Adenovirus Pneumonia. (8th August 2022) - Peng, Li; Liu, Silan; Xie, Tian; Li, Yu; Yang, Zhuojie; Chen, Yongqi; Deng, Liangji; Huang, Han; Ding, Xiaofang; Chen, Min; Lin, Lin; Wei, Sangzi; et al.
Abstract : Background . The study aimed to explore risk factors for bronchial mucus plugs (BMP) formation in children with adenovirus (AdV) pneumonia. Methods . A retrospective study was conducted on children with AdV pneumonia who underwent bronchoscopy from January 2019 to December 2019. Children were divided into the BMP group and the control group, depending on whether BMP was formed or not. The clinical information and treatment proposals of the two groups of children were counted and analyzed via multiple logistic regression analysis, ROC curve analysis, and correlation analysis. Results . Among 453 patients with AdV pneumonia, 185 (40.84%) were in the BMP group. Among all the cases, there were 188 patients with a single AdV infection, including 64 (34.04%) in the BMP group and 124 (65.96%) in the control group. The incidence of dyspnea, poor spirits, mixed infections, and other symptoms in the BMP group was higher than in the control group. Children in the BMP group had a longer heat range. C-reactive protein (CRP), lactate dehydrogenase (LDH), D-dimer (DD), and AdV load levels were higher in the MBP group. AdV load, Mycoplasma coinfection, DD, heat range, and LDH were independent risk factors for BMP, among which AdV load was the most significant (AUC = 0.819). AdV load was positively correlated with other risk factors, respectively. AdV load and heat range were independent risk factors for BMP patients with a single AdV infection. Conclusion . AdV load might have important clinical value in predicting BMP development in AdV pneumonia.